Respostas

A melhor resposta!
2013-11-30T08:08:42-02:00
Primeiro tem que resolver o produto notavel,

(x+3)^2=1

x²+2.x.3 +  3² = 1
x² + 6x + 9 - 1 = 0
x² + 6x + 8 =0 

resolvendo baskara

delta = b² - 4ac
delta = 6² - 4.1.8
delta = 36 - 32
delta = 4

-b+-Vdelta / 2a
-6 +- 2 /  2
x¹=  -4/2 = -2
x²= -8/2 = -4
3 3 3
valeu mesmo
sinalize a melhor resposta..
ta
tem q espera aparece neh
2013-11-30T08:43:45-02:00
(x+3)² = 1
x²+6x+9-1=0
x²+6x+8 = 0 
Δ = b²-4ac
Δ = 6²-4.1.9
Δ = 36 - 36
Δ = 0
x' = x" = -b/2a
x' = x" = -6/2
x' = x" = -3
S: {-3}
1 2 1